SISTEM INFORMASI JUAL BELI BIBIT TANAMAN PADA UNIT USAHA PERTANIAN DAERAH LHOKSEUMAWE - , FIRDA ANDIKA, Muh Fakhurrifqi, S.Kom. M.Kom ([Yogyakarta] : Universitas Gadjah Mada, 2014)
As a result of the development of science and information technology, the performance of an agency, especially agricultural business unit, requires not only appropriate, but also must be fast in data management. This demand will not be completed if the data management is still manual and use paper media that are easily damaged. Therefore, it is necessary for an information system to help managing the data in units of agricultural businesses. The buying and selling plant seeds information system is one of the important systems in crop seed sales in the agricultural business units. As the name suggests, this system is used to help managing the data and the data transaction seedlings in the agricultural business units. This system can be used for the data management such as the data and transaction seeds. The system of buying and selling seeds of this plant also has features such as: printed memorandum of buyers and monthly reports.